Over a million students use our free study notes to help them with their homework
The question tells us the ratio between two algebraic expressions is the same as the ratio between 2 other algebraic expressions. So, we can re-write the equation as (2x-1)/(x-4) = (16x+1)/(2x-1)Re-arrang...
Start by differentiating x2 – 3xy – 4y2 + 64 = 0 with respect to x to obtain an equation in x, y and dy/dx: 2x – 3y – 3x.dy/dx – 8y.dy/dx = 0 [use the product rule to differe...
As we are integrating, we must decide which method to use. As the integrand is of the form f(x)*g(x), integration by parts seems to make sense. Firstly, let L = INT(sin(x)*e^x). So we want to find L - thi...
Starting with: 2tanθsinθ = 4 - 3cosθ . We can rewrite tanθ in terms of sinθ and cosθ.We know: tanθ = sinθ ÷ cosθ .By substituting we get: 2(sinθ ÷ cosθ)sinθ = 4 - 3cosθ .Let's multiply out by cosθ to get:...
9sin(x) + 12 cos(x) = Rsin(x+y) =R(sin(x)cos(y)+cos(x)sin(y))= (Rcos(y))sin(x) + (Rsin(y))cos(x)Therefore by matching the coefficientsRsin(y)=12, Rcos(y)=9 [1]SoRsin(y)/Rcos(y) = 12/9 = 4/3, therefore tan...
←
338
339
340
341
342
→
Internet Safety
Payment Security
Cyber
Essentials